Research progress on polyoxometalate-based transition-metal–rare-earth heterometallic derived materials: synthetic strategies, structural overview and functional applications. Issue 24 (19th February 2016) - Zhao, Jun-Wei; Li, Yan-Zhou; Chen, Li-Juan; Yang, Guo-Yu
Abstract : This review summarizes the structural types of reported polyoxometalate-based transition-metal–rare-earth heterometallic derived materials (PTRHDMs) together with synthetic strategies, structural motifs and relevant functional applications. Abstract : With the rapid development of science and technology and the trend of multidisciplinary pervasion, POM-based TM–RE heterometallic chemistry (POM = polyoxometalate, TM = transition-metal, RE = rare-earth) has become one of the most rapidly growing and challengeable areas of inorganic chemistry due to the impressive structural diversities, various chemical compositions and potential applications of these materials in magnetism, optics, electrochemistry, electrocatalysis and materials science. Over the past several years, continuous interest and persisting efforts have been dedicated to the preparation and exploration of POM-based TM–RE heterometallic derived materials (PTRHDMs), which have led to more than two hundred PTRHDMs. In this review, we summarize the structural types of reported PTRHDMs together with synthetic strategies, structural motifs and relevant functional applications. The exciting array of this emerging research theme presages continuous growth and great vitality. In the last section, some prospects of this branch are also presented and possible guidance for future work is outlined.